Muslim academics’ knowledge sharing in Malaysian higher learning institutions - Fauzi, Muhammad Ashraf; Tan, Christine Nya-Ling; Thurasamy, Ramayah; Ojo, Adedapo Oluwaseyi; Shogar, Ibrahim Adam Ahmed (Emerald Publishing Limited, 2019)
Purpose – The purpose of this paper is to investigate Muslim academics’ knowledge sharing (KS) behavior and its relating predictors in the context of Malaysia. Academics being the center entity of education in higher learning institutions (HLI) has the noble obligation in spreading and sharing knowledge. Moreover, in Islamic teaching, academics having knowledge must let others know that knowledge can be beneficial in everyday life. Design/methodology/approach – The underpinning theories used in this study are theory of planned behavior (TPB) and social capital theory (SCT) for assessing the probable factors that can determine academics’ KS behavior. This study evaluates 398 Muslim academics in Malaysia for KS behavior in 20 public and 5 private HLIs. Structural equation modeling–partial least square was used as the tool for data analysis. Findings – It was found that all the variables tested in this study were significant, except for commitment. Social network, trust, management support, facilitating conditions and social media are significant predictors in Muslimacademics’ KS behavior.